Answer:
(-2,8)
Step-by-step explanation:
8x + 9y=56
-9x + y = 26
---------------------------------------------------------------------------------
-9x + y = 26
+9x = +9x
y = 9x + 26
---------------------------------------------------------------------------------
8x + 9(9x+26) = 56 <-- substitute for y from above
8x + 81x + 234 = 56
89x + 234 = 56
- 234 = - 234
89x = - 178
x = -2 <--- we got the x value!!
--------------------------------------------------------------------------------
-9x + y = 26
-9 (-2) + y = 26 <-- substitute for x from above
18 + y = 26
- 18 = - 18
y = 8 <-- we got the y value!!